2016
DOI: 10.1111/1475-6773.12550
|View full text |Cite
|
Sign up to set email alerts
|

Meaningful Use of Electronic Health Records and Medicare Expenditures: Evidence from a Panel Data Analysis of U.S. Health Care Markets, 2010–2013

Abstract: Health care markets that had steeper increases in EHR penetration during 2010-2013 also had steeper decreases in total Medicare and acute care expenditures per beneficiary. Markets with greater increases in physician EHR had greater declines in Medicare Part B expenditures per beneficiary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 34 publications
1
11
0
Order By: Relevance
“…Focusing practice purchases toward physicians achieving MU could have benefited organizations by smoothing the assimilation process and by reducing the need for software purchases or training while allowing them to maximize the accompanying subsidies from the HITECH Act. Vertically integrated systems may have also helped facilitate improved quality and coordination of care offered to patients—consistent with some recent evidence …”
Section: Discussionsupporting
confidence: 68%
“…Focusing practice purchases toward physicians achieving MU could have benefited organizations by smoothing the assimilation process and by reducing the need for software purchases or training while allowing them to maximize the accompanying subsidies from the HITECH Act. Vertically integrated systems may have also helped facilitate improved quality and coordination of care offered to patients—consistent with some recent evidence …”
Section: Discussionsupporting
confidence: 68%
“…Our results show that the growth in adoption and use of EHRs by physicians in ambulatory care settings has a modest negative association with ACSC admissions among chronically ill Medicare patients that is consistent with policy goals. For further context, we note that in a separate analysis reported elsewhere we estimated approximately $1.6 billion in reductions for Medicare Part A acute care expenditures among the same population of patients as in this study that was associated with the increase in physician ambulatory care EHR use during 2010–2013 (Lammers and McLaughlin ). It is likely that these expenditure reductions are due in large part to the reduction in ACSC admissions found in this study.…”
Section: Discussionmentioning
confidence: 57%
“…1 Particularly for patients with expensive chronic ambulatory care-sensitive conditions, such as diabetes, the use of EHR systems in primary care is regarded as having important potential to improve care provision through improved organization and exchange of patient information. 2 The association of EHR systems in primary care with health care utilization has been investigated, with some evidence of improvements in health care delivery and outcomes. Evidence has shown that implementation of EHR systems may be associated with reductions in emergency visits and hospital admissions among patients with diabetes.…”
Section: Introductionmentioning
confidence: 99%